Device closure of congenital ventricular septal defects with Amplatzer devices: first experiences in Turkey - Celiker, Alpay; Ozkutlu, Süheyla; Karagöz, Tevfik; Erdoğan, Ilkay; Ozer, Sema; Aypar, Ebru (The Turkish Journal of Pediatrics, 2008)
Ventricular septal defects (VSD), which cause volume overload, may be closed by interventional method. The success depends on the precise anatomic definition of the defect and its relation to other cardiac structures. We report our first experiences of transcatheter closure of perimembranous and muscular VSD. Between May 2005 and September 2006, transcatheter closure of VSD was attempted in 38 patients. Implantation was successful in 37 patients. In one patient, the procedure failed because of the long sheath kinking. We observed important complications in three patients: severe tricuspid valve regurgitation, residual VSD and tricuspid valve regurgitation and right bundle branch block in the short-term follow-up. Transcatheter device closure with Amplatzer device seems to be effective and safe in the treatment of perimembranous and muscular VSDs. Tricuspid valve incompetence may cause problems. Long-term results are required to determine the efficacy and safety.